L’hyperthème et le thème généralisant dans la structure informationnelle du discours - Miczka, Ewa (Neophilologica, 2013)
In this paper the author analyses the role of global and generalising themes in the information structure of discourse defined as hierarchically organized thematic-rhematic structures. In their thematic part, the author distinguishes three levels represented by: (1) global theme, (2) themes of thematic segments and generalising themes, and (3) themes of sentences. The author focuses her attention on possible localisation and functions of global and generalising themes in discourse.